Membentuk Karakter Hamba Tuhan Melalui Pendidikan Teologi Di Sekolah Tinggi Agama Kristen Nabire - Nawipa, Yance (CV. Creative Tugu Pena, 2024)
The determinant of success in the service of a servant of God is being supported by good and correct character. Various efforts have been made by educational institutions to implement character formation in the learning process. However, how is it possible to succeed in ministry if you do not have good character, like the character of Christ? The aim of this research is to revitalize teaching in forming the character of a servant of God through Theological Education at the Nabire Christian College. The method used involves interviews as a primary data source and collection of library data related to this topic. The research results show that the character of a servant of God in the field of theology is still relevant and can be integrated into Theological Education at the Nabire Christian College. The conclusion of this research is that the character of a servant of God, which is instilled through Theological Education, is very necessary in carrying out services, especially in schools, churches and congregations. Keywords: Education Character, Educational Teology, Good Character